2014
DOI: 10.3389/fmicb.2014.00327
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing detects human and animal pathogenic taxa in the grapevine endosphere

Abstract: Generally, plants are not considered as hosts for human and animal pathogens (HAP). The recent produce-associated outbreaks of food-borne diseases have drawn attention toward significant deficiencies in our understanding of the ecology of HAP, and their potential for interkingdom transfer. To examine the association of microorganisms classified as HAP with plants, we surveyed the presence and distribution of HAP bacterial taxa (henceforth HAPT, for brevity's sake) in the endosphere of grapevine (Vitis vinifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
(72 reference statements)
1
22
0
Order By: Relevance
“…The latter seems rather unlikely given the number of strains recovered and their phylogenetic diversity. Moreover, earlier studies using cultivation-independent techniques also identified OTUs (operational taxonomic units) affiliated with the genera Bacillus and Staphylococcus in the endosphere of grapevine, although not to such a great extent as that observed in our study Yousaf et al, 2014). Interestingly, the vineyard from which we sampled our leaf material is an organically managed one and OTUs affiliated with Staphylococcus have been reported to be more abundant in organically managed fields than in conventional ones (Campisano et al, 2014).…”
Section: Resultssupporting
confidence: 52%
“…The latter seems rather unlikely given the number of strains recovered and their phylogenetic diversity. Moreover, earlier studies using cultivation-independent techniques also identified OTUs (operational taxonomic units) affiliated with the genera Bacillus and Staphylococcus in the endosphere of grapevine, although not to such a great extent as that observed in our study Yousaf et al, 2014). Interestingly, the vineyard from which we sampled our leaf material is an organically managed one and OTUs affiliated with Staphylococcus have been reported to be more abundant in organically managed fields than in conventional ones (Campisano et al, 2014).…”
Section: Resultssupporting
confidence: 52%
“…In this study we identified 96 genera and discriminated over 30 species that were present during wine fermentation. Importantly, most of the species we detected have not been reported previously during wine fermentation (Table S4 ), with the exception of a few species (i.e., Propionibacterium acnes, Bacillus thermoamylovorans, Pseudomonas stutzeri ) that were isolated from grapevine, palm wine, and wine corks (Combet-Blanc et al, 1995 ; Bañeras et al, 2013 ; Yousaf et al, 2014 ). The genus Gluconobacter increased significantly during organic fermentation (from 3.28 to 49.42%), while it exhibited less notable changes during the conventional fermentation (from 5.63 to 7.57%) process (Table 3 ).…”
Section: Discussionmentioning
confidence: 71%
“…Yousaf and collaborators 75 , by pyrosequencing approach, found opportunistic human pathogens in the grapevine endosphere; in this work, four bacterial genera (Burkholderia, Propionibacterium, Staphylococcus and Clostridium), which include opportunistic human pathogens, were detected. In the same year, Campisano and colleagues reported the presence of opportunistic human pathogens in grapevine 76 .…”
Section: Discussionmentioning
confidence: 59%